Shari‘a as Customary Law? An Analytical Assessment from the Nigerian Constitution and Judicial Precedents - Jamiu Muhammad Busari (AHKAM : Jurnal Ilmu Syariah, 2021)
Under the Nigerian legal classification, shari‘a, the Islamic legal system is classified as customary law. It is on these premises that the Muslims’agitations for full-fledge shari‘a applications and declassification from being a customary law are always thwarted and termed “unconstitutional” by the shari’a antagonists. Meanwhile, the Muslims and protagonists viewed the problems as judicial misinterpretations and legal incongruity. In this study, with the adoption of an analytical approach, shari‘a and customary law are assessed from the provisions of the Nigerian Constitutions and some judicial precedents to unravel the actual position of shari‘a. It was then discovered that, despite the classification under the Nigerian legal system, shari‘a could not have been a customary law due to some factors which include its sources, divinity, permanency, and universality.AbstrakDalam hukum Nigeria, hukum Islam atau syariah diklasifikasikan sebagai hukum adat.  Premis itulah yang menjadi agitasi upaya penerapan syariah secara penuh oleh umat Islam. Usaha untuk pendeklasifikasi  hukum adat selalu digagalkan dan dianggap  “inkonstitusional” oleh penentang syariah.  sementara  sebagian Muslim dan pendukung syariah memandang masalah tersebut sebagai salah tafsir yudisial dan ketidaksesuaian hukum. Dalam penelitian ini, dengan  memakai pendekatan analitis, syariah dan hukum adat dinilai untuk mempertegas dalam  ketentuan Konstitusi Nigeria berdasar  beberapa preseden yudisial untuk mengungkap posisi syariah yang sebenarnya. Kemudian ditemukan bahwa, meskipun klasifikasi di bawah sistem hukum Nigeria, syariah tidak bisa menjadi hukum adat karena beberapa faktor yang meliputi sumbernya, keilahian, keabadian,  dan universalitas.